Analysis Of Factors That Influence Motivation In Learning Mathematics - Finuya, Hiftinia (Yana Research, 2022)
There are several reasons why education in Indonesia does not go according to plan. One of the reasons is the number of underdeveloped talents of students. This raises the question why it can happen. So one of the reasons is because there is no proper motivation for students. For this reason, we investigated what factors influence students' motivation in learning mathematics at the location of SMP Negeri 2 Binjai, precisely in class IX-1 which consists of 15 students to see what factors influence their learning motivation in learning mathematics. By using quantitative research methods by giving questionnaires to respondents so that research data are in the form of numbers and analysis using pie charts. Based on the results of the study, it was found that there were several factors that influenced the motivation in learning mathematics for class IX-1 students of SMP Negeri 2 Binjai. These factors include: the ideals or aspirations of students, interests, the role and position of the teacher in teaching students, the desire and willingness to learn, learning expectations, praise from the teacher, and interest in the material/lesson. So, based on these factors, it is known that the types of motivation possessed by class IX-1 students of SMP Negeri 2 Binjai are Intrinsic Motivation and Extrinsic Motivation